Солдатлэн данэз: кылбуръёс но поэмаос / Николай Байтеряков - Байтеряков Николай Семенович (Удмуртия, 1987)
Экземпляры: АБ (20140430) / Инвентарный номер: 15113 / Сис.шифр: С(Удм) / Авт.знак: Б 18 / ГРНТИ: 17.82.10 / ББК: 84(Удм)^VLBC/RL